2014
DOI: 10.1161/circulationaha.113.005287
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Long-Term Outcomes in Patients With Significant Myxomatous Mitral Regurgitation Undergoing Exercise Echocardiography

Abstract: 2, 31±12 mm Hg, 46±17 mm Hg, 9.6±3, and 33±14 beats, respectively. During 6.4±4 years of follow-up, there were 87 events. On stepwise multivariable Cox analysis, percent of age/sex-predicted metabolic equivalents (hazard ratio, 0.99; 95% confidence interval, 0.98-0.99; P=0.005), heart rate recovery (hazard ratio, 0.29; 95% confidence interval, 0.17-0.50; P<0.001), resting right ventricular systolic pressure (hazard ratio, 1.03; 95% confidence interval, 1.004-1.05; P=0.02), atrial fibrillation (hazard ratio, 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(38 citation statements)
references
References 47 publications
0
36
0
2
Order By: Relevance
“…5 However, many patients are unaware of the onset of symptoms because of their gradual onset and their unwitting ability to subtly reduce exercise to prevent symptoms from occurring. 8 Furthermore, LV dysfunction is difficult to assess in severe MR, and LV contractility may already be irreversibly impaired, even though left ventricular ejection fraction (LVEF) remains in the usual normal range. Previous reports have shown that outcome after MV surgery is impaired once preoperative LVEF is <60%, and, thus, an LVEF <60% is considered abnormal and a potential indication for surgery in severe MR. 3 Additionally, impaired LVEF postoperatively (<50%) has been shown to predict poorer long-term survival.…”
mentioning
confidence: 99%
“…5 However, many patients are unaware of the onset of symptoms because of their gradual onset and their unwitting ability to subtly reduce exercise to prevent symptoms from occurring. 8 Furthermore, LV dysfunction is difficult to assess in severe MR, and LV contractility may already be irreversibly impaired, even though left ventricular ejection fraction (LVEF) remains in the usual normal range. Previous reports have shown that outcome after MV surgery is impaired once preoperative LVEF is <60%, and, thus, an LVEF <60% is considered abnormal and a potential indication for surgery in severe MR. 3 Additionally, impaired LVEF postoperatively (<50%) has been shown to predict poorer long-term survival.…”
mentioning
confidence: 99%
“…The right contractile property is important because right ventricular remodeling may play an important role in clinical outcome of patients undergoing mitral valve surgery [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…62 Alashi et al examined 448 asymptomatic patients with severe primary mitral regurgitation and preserved ejection fraction and demonstrated that abnormal longitudinal strain and higher BNP levels are associated with higher long-term mortality and the combination of two appeared to be a synergistic outcome predictor. 63 The importance of exercise capacity in predicting outcomes in patients with severe primary regurgitation was studied by Naji et al 64,65 In 576 patients with primary mitral regurgitation who underwent exercise echocardiography prior to mitral valve surgery, lower achieved METs were associated with worse long-term outcomes. The authors concluded that achieving >100% of age and gender-predicted METs can safely delay mitral valve surgery for at least one year, without an effect on outcomes.…”
Section: Natural History Progression and Predictors Of Outcomes In Mmentioning
confidence: 99%